Exchange rates forecasting model: an alternative estimation procedure - Baharumshah, Ahmad Zubaidi; Liew, Khim Sen; Lim, Kian Ping (Universiti Putra Malaysia Press, 2004)
This study proposes an alternative procedure for modelling exchange rates behaviour, which is a linear combination of a long-run function and a short-run function. Our procedure involves modelling of the long-run relationship and this is followed by the short-run function. Among all the possible combinations of modelling techniques, we proposed the simplest form, namely modelling the long-run function by the well established purchasing power parity (PPP) based model and setting up the short-run function based on its time series properties. Results of this study suggest that our procedure yields powerful forecasting models as they easily outperform the simple random walk model-which is rarely defeated in the literature of exchange rate forecasting-in terms of out-of-sample forecasting, for all the forecast horizons ranging from one to fourteen quarters. This study provides us with some hope of achieving a reasonable forecast for the ASEAN currencies using the fundamental monetary model just by a simple adaptation.